Japan's Security Relations With China Since 1989 : From Balancing to Bandwagoning?. - Drifte, Reinhard (Routledge, 2002)
Japan's Security Relations with China since 1989 raises the crucial question whether Japan's political leadership is able to handle such a complex policy in the face of an increasing assertive China and an US alliance partner with strong swings.